Vascular Plants of Alberta, Part 1 Ferns, Fern Allies, Gymnosperms, and Monocots - Joyce Gould, A. (University of Calgary Press, 2017)
Vascular Plants of Alberta is a user-friendly, portable key to the ferns, fern allies, gymnosperms, and monocots of Alberta. This key to the species of Alberta will delight all those interested in botany, with its intuitive and exhaustive presentation of the plants, including new names and taxonomical understandings that have emerged in recent years. Designed to be carried into the field for handy reference and use, Vascular Plants of Alberta presents: -A list of all species, native and introduced, known to occur in Alberta, arranged alphabetically -Information on scientific names of taxa and their synonyms -Keys for identifying taxa, including infra specific -Descriptions of the major taxonomic categories -Discussion about taxonomic problems and relationships of the taxa -Distribution and habitat information for native species -Descriptions for new taxa